Effect of run training and cold-water immersion on subsequent cycle training quality in high-performance triathletes. - Rowsell, G. J.; Reaburn, P.; Toone, R.; Smith, M.; Coutts, A. J. (The Journal of Strength and Conditioning Research, 2014)
The purpose of the study was to investigate the effect of cold-water immersion (CWI) on physiological, psychological, and biochemical markers of recovery and subsequent cycling performance after intensive run training. Seven high-performance male triathletes (age: 28.6 ± 7.1 years; cycling VO2peak: 73.4 ± 10.2 ml/kg/min) completed 2 trials in a randomized crossover design consisting of 7 × 5-minute running intervals at 105% of individual anaerobic threshold followed by either CWI (10 ± 0.5° C) or thermoneutral water immersion (TNI; 34 ± 0.5° C). Subjects immersed their legs in water 5 times for 60 seconds with 60-second passive rest between each immersion. Nine hours after immersion, inflammatory and muscle damage markers, and perceived recovery measures were obtained before the subjects completed a 5-minute maximal cycling test followed by a high-quality cycling interval training set (6 × 5-minute intervals). Power output, heart rate, blood lactate (La), and rating of perceived exertion (RPE) were also recorded during the cycling time-trial and interval set. Performance was enhanced (change, ±90% confidence limits) in the CWI condition during the cycling interval training set (power output [W/kg], 2.1 ± 1.7%, La [mmol/L], 18 ± 18.1%, La:RPE, 19.8 ± 17.5%). However, there was an unclear effect of CWI on 5-minute maximal cycling time-trial performance, and there was no significant influence on perceptual measures of fatigue/recovery, despite small to moderate effects. The effect of CWI on the biochemical markers was mostly unclear, however, there was a substantial effect for interleukin-10 (20 ± 13.4%). These results suggest that compared with TNI, CWI may be effective for enhancing cycling interval training performance after intensive interval-running training.